Primary structure and tissue distribution of the orphanin FQ precursor. - Nothacker, H P (1996)
The heptadecapeptide orphanin FQ (OFQ) is a recently discovered neuropeptide that exhibits structural features reminiscent of the opioid peptides and that is an endogenous ligand to a G protein-coupled receptor sequentially related to the opioid receptors. We have cloned both the human and rat cDNAs encoding the OFQ precursor proteins, to investigate whether the sequence relationships existing between the opioid and OFQ systems are also found at the polypeptide precursor level, in particular whether the OFQ precursor would encode several bioactive peptides as do the opioid precursors, and to study the regional distribution of OFQ sites of synthesis. The entire precursor protein displays structural homology to the opioid peptide precursors, especially preprodynorphin and preproenkephalin. The predicted amino acid sequence of the OFQ precursor contains a putative signal peptide and one copy of the OFQ sequence flanked by pairs of basic amino acid residues. Carboxyl-terminal to the OFQ sequence, the human and rat precursors contain a stretch of 28 amino acids that is 100% conserved and thus may encode novel bioactive peptides. Two peptides derived from this stretch were synthesized but were found to be unable to activate the OFQ receptor, suggesting that if they are produced in vivo, these peptides would likely recognize receptors different from the OFQ receptor. To begin analyzing the sites of OFQ mRNA synthesis, Northern analysis of human and rat tissues were carried out and showed that the OFQ precursor mRNA is mainly expressed in the brain. In situ hybridization of rat brain slices demonstrated a regional distribution pattern of the OFQ precursor mRNA, which is distinct from that of the opioid peptide precursors. These data confirm that the OFQ system differs from the opioid system at the molecular level, although the OFQ and opioid precursors may have arisen from a common ancestral gene.